Assets management and faults rectifying system - Muzanenhamo, Godfrey. T. (Midlands State University, 2019)
The purpose of this project, the Zimbabwe Electricity Transmission and Distribution Company (ZETDC) Assets management and faults rectifying system was based on the provision of an indepth and detailed records of newly acquired assets and faults reports. Assets acquired are maintained and monitored by the system. Automatically the system schedules attention on assets that needs maintenance and those that require to be disposed. Faults rectification process was instigated as a result of detailed work arising information from users that is the employees. The Information Technology (I.T) department that consist of the systems administrator and the technicians, is responsible for using the system and they keep a constant checkout on the system for assets and faults management purposes. A range of software tools were proposed in developing the new system and interfaces were modelled and designed using CS8 Dreamweaver. The database implemented using the MySQL. The data collection method used included the observations, interviews as well as the questionnaires. These data collection methods helped in coming out with a valid research and supported the notion that advocated for the development of a new system that endeavored to address the perceived gap between the desired state and the existing state. In pursuit of the above, the documentation of the research project discussed five detailed chapters namely the introduction phase, planning phase, analysis phase, design phase and implementation phase. Apart from the listed the proposed system was user friendly and able to meet the non-functional requirements of the system. An ongoing maintenance would be useful throughout the course operation of the system.